Comparative persistence and adherence with newer anti-hyperglycemic agents to treat patients with type 2 diabetes in the United States. (1st December 2016) - Cai, Jennifer; Wang, Yuexi; Baser, Onur; Xie, Lin; Chow, Wing
Abstract: Objectives: Non - adherence and non - persistence to anti - hyperglycemic agents are associated with worse clinical and economic outcomes in patients with type 2 diabetes. This study evaluated treatment persistence and adherence across newer anti - hyperglycemic agents (canagliflozin, dapagliflozin, sitagliptin, saxagliptin, linagliptin, liraglutide, or exenatide). Methods: This retrospective cohort study of Truven Health Analytics Marketscan databases included adult patients with type 2 diabetes whose first pharmacy claim for a newer anti - hyperglycemic agent was between February 1, 2014 and July 31, 2014. Treatment persistence and adherence were assessed for 12 months after the first claim (post-index). Persistence was defined as no gap ≥ 90 days between the end of one pharmacy claim and the start of the next pharmacy claim post-index. Adherence used two definitions: proportion of days covered (PDC) and medication possession ratio (MPR). Multivariable analyses of non - persistence (hazard ratios) and adherence (odds ratios) were adjusted for baseline demographics, drug cost, clinical characteristics, and other anti - hyperglycemic agents. Results: A total of 11, 961 patients met all study selection criteria. Persistence rates at 12 months were significantly greater ( p < 0.05 for each comparison) for canagliflozin 100 mg (61%) compared with dapagliflozin 5 mg (40%), dapagliflozin 10 mg (41%), sitagliptin (48%), saxagliptin (42%), linagliptin (52%), liraglutide (47%), exenatide (23%), and long-acting exenatide (39%). The persistence rate was greater ( p < 0.05) for canagliflozin 300 mg (64%) vs canagliflozin 100 mg. Median adherence rates for canagliflozin 100 mg (MPR = 0.83; PDC = 0.79) and canagliflozin 300 mg (MPR = 0.92; PDC = 0.81) were greater than for the other index anti - hyperglycemic agents (MPR = 0.33 – 0.75; PDC = 0.33 – 0.72). Consistent results for treatment persistence and adherence were observed in multivariable analyses that were adjusted baseline characteristics. Conclusions: Canagliflozin was associated with better treatment persistence and treatment adherence compared with other anti - hyperglycemic agents in real-world settings.